Advancing Africa’s food systems transformation through CAADP: research and the role of livestock - Covic, Namukolo M. (International Livestock Research Institute, 2025)
Exploring the role and impact of the Comprehensive Africa Agriculture Development Programme (CAADP) in transforming Africa’s food systems and advancing progress toward the Sustainable Development Goals. It examines achievements and lessons from CAADP’s implementation over the years. Also highlighting how ILRI and CGIAR’s research and innovations align with CAADP priorities to strengthen food security, nutrition, and resilience across the continent.